2012
DOI: 10.2147/opth.s29660
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outcomes of conventional WaveLight® Allegretto Wave® and Technolas® excimer lasers in myopic laser in situ keratomileusis

Abstract: ObjectiveTo compare the results of laser in situ keratomileusis for myopia using WaveLight® Allegretto Wave® Eye-Q® and Technolas® 217z excimer lasers.MethodA retrospective, comparative case series of 442 eyes matched for age and myopia: half each were treated with Allegretto’s wavefront-optimized algorithm and Technolas PlanoScan. Outcome measures were postoperative mean logarithm of the minimum angle of resolution (logMAR) uncorrected visual acuity (UCVA), manifest refraction spherical equivalent (MRSE), cyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 28 publications
1
16
1
Order By: Relevance
“…The proportions of eyes achieving postoperative manifest refraction SE in the −0.50 to 0.00 D range was more than 87% at the 12-month visit (Figure 6); 95.7% were within ±1.0 D at the 1-year results. These results compare very favorably to other studies,21 in which for the same range of ±1.0 D, the proportions were in the range of 98%.…”
Section: Discussionsupporting
confidence: 88%
“…The proportions of eyes achieving postoperative manifest refraction SE in the −0.50 to 0.00 D range was more than 87% at the 12-month visit (Figure 6); 95.7% were within ±1.0 D at the 1-year results. These results compare very favorably to other studies,21 in which for the same range of ±1.0 D, the proportions were in the range of 98%.…”
Section: Discussionsupporting
confidence: 88%
“…The efficacy index per eye with the Triple-A profile is better than that reported in a comparison of the Wavelight ® Allegretto Wave ® and Technolas ® by Han et al17 and with the Schwind Amaris ® platform (SCHWIND eye-tech-solutions GmbH, Kleinostheim, Germany) used by Alio et al19 The efficacy index per eye with the Triple-A profile (1.02–1.04) in our study is also slightly better than the efficacy index per eye calculated with data from the US Food and Drug Administration (FDA) clinical trial on the Carl Zeiss MEL 80 platform (0.99) 21…”
Section: Discussioncontrasting
confidence: 63%
“…This value is lower than those reported by several studies 17,1921. The UDVA results from different studies can be compared in terms of the efficacy index instead of a direct comparison of UDVA, as UDVA results are subject to individual differences introduced by physicians.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The platform offers the ability to import into the laser treatment planning mode the topographic data from the Placido-disk topographer (Vario, WaveLight) and topometry data from a Scheimpflug-based device (Oculyzer II-WaveLight), and accordingly customize the excimer treatment to the cornea (eg, for topography-guided treatment) 12. This study and previous studies have reported extensively the applications of topography-guided treatments with these platforms in irregular and normal eyes 2229…”
Section: Discussionmentioning
confidence: 99%